Unobtrusive Loudspeaker Selection for Sound Installations - Kerem Ergener (My University, 2021)
In the world of sound-based art installations a visual aspect of sound is often neglected. Loudspeakers come many shapes and sizes but finding the right loudspeaker can be a daunting task. Especially the venue which the installation is presented, and budgetary limitations can create many problems. Visual aspect of the design of loudspeakers can take away from the effect that the sound installation is trying to achieve. In most of the cases artists mostly interested in the sound and visual parts of the installation they created is neglected. Therefore, the loudspeakers need to be inconspicuous and unobtrusive. This paper focuses on choice of loudspeakers that will not interfere with installation itself and it is affordable enough that can be install at any venue. Through this research different types of speaker designs are investigated, and their pros and cons are compared. Commercial to do-it-yourself methods is discussed. Sound reproduction through sound exciters and their use to make different objects to become sound emitters is examined and use of such loudspeakers is advised.
Keywords: Speech and Audio Processing; Music Technology and Sound Studies; Hearing Loss and Rehabilitation